Kekerasan dalam Film “Galaksi” (Analisis Isi Kualitatif) - Arsyadani, Robby; Hariyati, Farida; Rahmawati, Yulia (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2024)
The movie Galaksi is a movie adapted from Poppi Pertiwi's novel is a movie that tells about life and romance in high school. In the movie, there are many scenes of violence and this research aims to describe the forms of violence contained in the movie